Mothers’ Identities and Parenting in Amy Tan's The Joy Luck Club (1989) - Paramitha, Nadya Aulia Cinta (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
Parenting and identity are two topics that coexist, especially in the context of literature. Amy Tan’s The Joy Luck Club (1989) includes the topic of parenting, especially between mothers and their daughters, and the development of someone’s identity. However, the connection between the mothers’ identity and the parenting tendency in the novel is rarely explored. Therefore, the novel The Joy Luck Club, especially three of four mothers, An-mei Hsu, Lindo Jong, and Ying-Ying St. Clair, is used as the object of the research because there are depictions of the correlation between identity and childhood experiences, as well as between identity and parenting. This study aims to examine the connection between the mothers’ identities to their childhood experiences, and also the relationship between the identities of mothers with their parenting tendencies. To complete those targets, Erik Erikson’s theory about identity will be the basis to find a connection between their identities and their childhood experiences, then collaborating it with Diana Baumrind’s classification on parenting to find the relation between the identities and their parenting tendencies. The analysis will be supported by Erikson’s definition of identity and Baumrind’s classification of parenting. The findings of this study reveal that mothers’ identities in Amy Tan’s The Joy Luck Club (1989) are related to their childhood experiences. Moreover, it also discovers how their identities are related to their parenting tendencies according to Baumrind’s classification.